Design of rectangular microstrip patch antenna with two enhancements (bandwidth and gain) - Aswad, Fadhil M.; Mohamad Zainol Abidin, Abd Aziz; Ho, Yih Hwa (2015)
This electronic document introduces a design of a rectangular patch antenna with L-probe feed at frequency of 2.4 GHz and a design strategy using a dual-band frequency selective surface (FSS) consisting four arrays of double rectangular ring elements to improve the bandwidth and gain, and to optimize the onsets of two operating frequencies foe a U-slot patch antenna is presented. After implanting the FSS in the U-slot patch antenna, it is found that the bandwidth have been improved from 3.14 % to 5.51 % at resonant frequencies 2.4 GHz. The U-slot patch antenna implanted with a FFS consisting of double rectangular ring elements is capable of dual-band operations at 2.4 GHz. The radiation patterns are satisfied at this band. This paper aims to introduce an improvement of the gain parameter of a microstrip patch antenna with inset L-probe feed by using the four arrays double rectangular ring element. And aims to introduce an improvement of the bandwidth by using U-slot microwave patch antenna. This improvement will be investigated using the CST simulator. The design is performed at the frequency of 2.4 GHz.